Increased effective piezoelectric response of structurally modulated P(VDF-TrFE) film devices for effective energy harvesters. (July 2020) - Hu, Xinping; Yu, Shuhui; Chu, Baojin
Abstract: The low piezoelectric response (piezoelectric coefficient d33 lower than 30 pC N −1 ) of PVDF-based polymers limits their practical applications. Here we report a mechanical structure which can enhance the effective piezoelectric response of P(VDF-TrFE) copolymer. The polymer films were fabricated into a circular arch structure or arrays of arch structures. When a plane force was applied to the arch films, the force is concentrated at the outer rim of the arch structure. The effective piezoelectric response can be enhanced by >70 times because of the stress concentration and the measured effective piezoelectric response can be as high as 1990 pC N −1 . The arch films exhibit an enhanced energy harvesting performance when they are utilized as mechanical energy harvesting devices. The output power density was improved by >2700 times compared with that measured in the films without arch structure. An output power density of 9 mW cm −3 was achieved in the arch films under non-resonance frequency. These results indicate that the proposed polymer-based structure is promising for the practical applications in high-performance flexible piezoelectric devices. Graphical abstract: Unlabelled Image Highlights: A mechanical structure is proposed to significantly increase the piezoelectric response and energy harvesting performance of piezoelectric polymer films. The enhancement is caused by the stress concentration in the structure. The output power density of the energy harvester with the proposed structure is enhanced by more than 2700 times. A maximum output power density of 9 mW cm -3 is achieved in energy harvester with the structure under non-resonance frequency.